2005
DOI: 10.1002/app.22249
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of some polymers derived from modified amino polyacrylamide by reacting it with benzoate esters and benzaldehyde derivatives

Abstract: Functionalized polymers have gained much interest in the last decades. This is due to their functional groups and their polymer nature, which give them unique properties and more advantages than the corresponding small molecules. In this trend, we modified polyacrylamide by introducing an amino group in the side chain of the polymer by reacting it with ethylenediamine. The aminemodified polymer was reacted with two classes of active compounds. The first group is aromatic aldehydes containing active groups such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Poly-HEMA (PHEMA) is a favorable biomaterial because of its excellent biocompatibility and physicochemical properties similar to those of living tissues [5] . The polymerization of hydrophilic polymer such as PHEMA also improves the biodegrading properties [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Poly-HEMA (PHEMA) is a favorable biomaterial because of its excellent biocompatibility and physicochemical properties similar to those of living tissues [5] . The polymerization of hydrophilic polymer such as PHEMA also improves the biodegrading properties [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…The various synthetic compounds consist of favorable functional groups such as chalcone, amide, phosphonium, and quaternary ammonium units which offer active sites for the microbial pathogens and further act as disinfectants . This kind of functional group‐incorporated compounds is widely used to synthesize several biopolymers for the treatment against the bacterial and fungal‐affected diseases in living beings . The main advantages of these antimicrobial polymeric materials are being thermally and chemically stable, non‐volatile, and non‐permeable through the mammalian skin and also eco‐friendly to the environment .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is often reported that these groups significantly enhance their antimicrobial activities. 26 Antimicrobial agents such as phenols, naphthalene, anthracene, and fluorene derivatives interact with the surface of the cell and lead to cell death through disintegration of the cell membrane of microorganisms. [27][28][29][30][31] The existence of C=O, C=C, and -NH 2 functional groups in a polyacrylamide molecular chain along with phenyl, naphthyl, and thiophene molecules possesses an enormous biological applications.…”
Section: Introductionmentioning
confidence: 99%